2018
DOI: 10.1016/j.mib.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from simple marine models on the bacterial regulation of eukaryotic development

Abstract: Molecular cues from environmental bacteria influence important developmental decisions in diverse marine eukaryotes. Yet, relatively little is understood about the mechanisms underlying these interactions, in part because marine ecosystems are dynamic and complex. With the help of simple model systems, including the choanoflagellate Salpingoeca rosetta, we have begun to uncover the bacterial cues that shape eukaryotic development in the ocean. Here, we review how diverse bacterial cues — from lipids to macromo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…There is a growing interest in the role of metabolites as chemical mediators in cross-kingdom interactions within aquatic systems (22). Molecular cues from environmental bacteria can influence the growth, development, and morphogenesis of the eukaryotes (23). The importance of bacterial biofilms in inducing larval settlement and metamorphosis of marine invertebrates has been described, but few molecular cues produced by bacteria have been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing interest in the role of metabolites as chemical mediators in cross-kingdom interactions within aquatic systems (22). Molecular cues from environmental bacteria can influence the growth, development, and morphogenesis of the eukaryotes (23). The importance of bacterial biofilms in inducing larval settlement and metamorphosis of marine invertebrates has been described, but few molecular cues produced by bacteria have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our study found that four of six inducing strains were gammaproteobacteria, suggesting that gammaproteobacteria are important inducers of larval settlement and metamorphosis for M. sallei. Because colonizable surfaces in the ocean are often very limited, cues from biofilm bacteria growing on these surfaces might indicate to animals that there is a surface on which to settle (23). Furthermore, the presence of biofilms on surfaces indicates that the environment of the surfaces is suitable for the survival of organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Symbiotic microbes are still important agents in the life cycles of many organisms (Woznica & King, ). In addition to their being critical during normal embryonic development, symbiotic microbes help numerous organisms to mediate metamorphosis (Freckelton et al, ; Shikuma, Antoshechkin, Medeiros, Pilhofer, & Newman, ; Smith & Rajan, ).…”
Section: The Origin Of Multicellular Life Cyclesmentioning
confidence: 99%
“…Eukaryotes, including animals and their closest living relatives, choanoflagellates, encounter abundant and diverse bacteria in the environment (1)(2)(3). However, interactions among eukaryotes and bacteria can be challenging to study in animal models due to the complex physiology of the hosts and the large number of oftentimes unculturable bacteria present, each of which releases diverse molecules (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…1A; (14,15)). In addition, like many animals (2,16,17), S. rosetta undergoes important life history transitions in response to distinct bacterial cues. For example, a secreted (Fig.…”
Section: Introductionmentioning
confidence: 99%